Crystal structure of 1-propanethiol–Co2(dobdc) from laboratory X-ray powder diffraction data. Issue 1 (March 2020) - Lefton, Jonathan B.; Pekar, Kyle B.; Sethio, Daniel; Kraka, Elfi; Runčevski, Tomče
Abstract : Laboratory X-ray powder diffraction was used to solve and refine the crystal structures of appended guest molecules within the pores of metal–organic frameworks (MOFs). Herein, we report the crystal structure of 1-propanethiol adsorbed in the pores of Co2 (dobdc) (dobdc 4– = 2, 5-dioxido-1, 4-benzenedicarboxylate, MOF-74). Soaking the activated MOF in neat 1-propanethiol resulted in the formation of 1-propanethiol–Co2 (dobdc). The thiol appendant MOF maintained the crystal symmetry, with a rhombohedral space group R- 3 and unit-cell parameters a = 25.9597(9) Å, c = 6.8623(5) Å, and V = 4005.0(4) Å 3 . As expected, the thiol sulfur formed a bond with the open cobalt metal site. The alkane chain was directed toward the center of the pore, participating in numerous van der Waals weak interactions with neighboring molecules. For the final Rietveld refinement, soft restrains were applied using bond distances obtained by periodic density functional theory (DFT) geometry optimization.